The Effect of Service Quality on Customer Loyalty with Customer Satisfaction as an Intervening Variable at The Gade Coffee Balikpapan - Anindya Fariyah Hardiyanti; C. Prihandoyo; Dwi Taufik Rahman (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study examines the effect of service quality on customer loyalty with customer satisfaction as a mediating variable at The Gade Coffee Balikpapan. The research addresses inconsistent findings in prior studies regarding the mediating role of satisfaction in the relationship between service quality and loyalty, particularly within local coffee shop contexts in developing cities. A quantitative explanatory design was employed using purposive sampling of 170 customers who had made at least two purchases. Data were collected through structured questionnaires and analyzed using SMART PLS. The findings reveal that service quality has a positive and significant direct effect on customer loyalty and a strong positive effect on customer satisfaction. Customer satisfaction significantly influences customer loyalty and partially mediates the relationship between service quality and loyalty. The strongest relationship was observed between service quality and customer satisfaction, highlighting service performance as the primary determinant of customer evaluation. The study concludes that enhancing service quality is a strategic approach to fostering long-term customer loyalty, particularly when it effectively generates customer satisfaction in competitive service environments.